2023
DOI: 10.1167/iovs.64.4.16
|View full text |Cite
|
Sign up to set email alerts
|

Relative Myopic Defocus in the Superior Retina as an Indicator of Myopia Development in Children

Abstract: Purpose To investigate the role of peripheral refraction in children's myopization. Methods This 2-year study included 214 children (8–15 years old). Refraction across the retina (field of view: 60° × 36°) was measured with a custom-made aberrometer every year. Three datasets were established: dataset 1, 214 subjects from baseline to the first-year visit; dataset 2, 152 subjects from baseline to the second-year visit; and dataset 3, 59 initial emmetropes from baseline t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As age and axial length increased, the spherical equivalent decreased, and peripheral relative hyperopia increased, suggesting that relative peripheral hyperopia remains an important risk factor for axial elongation and myopia development in children with low-to-moderate myopia. Saunders 30 and Lan 31 conducted longitudinal studies and found that peripheral relative refraction was indicative of an increased risk for axial elongation and central myopia. However, as this was a cross-sectional study, it is not su cient to indicate that peripheral relative hyperopia accelerates myopia development 19,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…As age and axial length increased, the spherical equivalent decreased, and peripheral relative hyperopia increased, suggesting that relative peripheral hyperopia remains an important risk factor for axial elongation and myopia development in children with low-to-moderate myopia. Saunders 30 and Lan 31 conducted longitudinal studies and found that peripheral relative refraction was indicative of an increased risk for axial elongation and central myopia. However, as this was a cross-sectional study, it is not su cient to indicate that peripheral relative hyperopia accelerates myopia development 19,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Spherical equivalent refractive error (SER), astigmatism and higher order aberrations (HOA) were obtained for each retinal location (61 points in the horizontal meridian), 11,[20][21][22] and experimental condition. Pupil diameter was measured from three random Hartmann-Shack images using the VPR at each trial (61 images) and condition.…”
Section: Discussionmentioning
confidence: 99%
“…The sensor was able to provide a resolution of 1° in the visual field, as noted previously. 11,[20][21][22]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that myopia could start developing at the superior retina, gradually extending to the posterior eyeball, largely influenced by genetic factors. Notably, when emmetropic individuals transitioned to myopia, their ocular shape tended to change more in terms of height than width; these findings shed light on the complex interplay of factors in myopia development, particularly in the superior retina [ 30 ]. In our current study, the superior thickness was not the area most influenced by the lighting conditions evaluated, and the results revealed significant differences in eccentricity in both photopic and scotopic conditions when comparing the central and peripheral retina, leading to a reduced peripheral retinal curvature at the analyzed horizontal plane.…”
Section: Discussionmentioning
confidence: 99%